Pengaruh Disiplin Kerja, Motivasi Kerja, dan LingkunganKerja Terhadap Kinerja Karyawan BMT Atunnisadi Karanganyar - Sabana Putri, Safira; Sunarso; Sutarno (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Baitul Maal Wat Tamwil (BMT) is a microfinance institution that is operated on the principle of profit sharing, the development of which has increased from year to year. BMT is a microfinance institution which consists of two activities at once, namely Baitul Maal Wat Tamwil. The aim of this research is to analyze the significance of the influence of work discipline, work motivation and work environment on the performance of BMT Atunnisa employees. This research is a survey or questionnaire on BMT Atunnisa employees. Data types use qualitative and quantitative data. Data sources use primary data and secondary data. The population in this study were all employees at BMT Atunnisa, namely 40 respondents. The number of samples used in this research was 40 people. The sampling technique uses saturated sampling. Data collection techniques use questionnaires, observation, and literature study/documentation. Data analysis uses descriptive analysis, multiple linear regression test, t test, F test and coefficient of determination test.  The results of the research show that work discipline has a significant effect on the performance of BMT Atunnisa employees in Karanganyar, work motivation has a significant effect on the performance of BMT Atunnisa employees in Karanganyar and the work environment has a significant effect on the performance of BMT Atunnisa employees in Karanganyar. The F test results show a calculated F value of 12.496 with a significance value (p-value) of 0.000 < 0.05. The coefficient of determination test result (adjusted R²) is 0.469, meaning that the contribution of work discipline, work motivation and work environment to employee performance is 46.9%.